The Cat Who Wanted To Go Home - "Tomlinson, Jill" (Egmont, London, 2004 London, 2004)
After Suzy, the little French cat, finds herself in a hot-air balloon on its way to England, she tries to make her way back home to France
Keywords: Cats Fiction